The Role of Self-Regulated Learning in the Implementation of Project-Based Learning to Reduce Academic Procrastination in Scientific Writing Courses - Asri, Dahlia Novarianing; Cahyono, Bambang Eko Hari (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The high level of academic procrastination in the Scientific Writing course needs serious attention because, if left unchecked, it can result in failure to achieve academic achievement. The main focus of this study is to analyze the impact of Project-Based Learning Model on academic procrastination and examine the impact of Self-Regulated Learning as a mediating variable among students in Scientific Writing courses. This research uses an experimental research design. The research population was all students from the Faculty of Teacher Training and Education, Universitas PGRI Madiun, Indonesia, who were taking the Scientific Writing courses. A sample of 186 students was obtained by using the cluster random sampling technique. The instruments used were the Self-Regulated Learning scale and the academic procrastination scale. Data analysis includes descriptive data analysis, prerequisite tests, and inferential data analysis using a two-way ANOVA. The following research findings support the following findings: (1) students in the Scientific Paper course who received a project-based learning model showed significantly higher levels of academic procrastination than students who received a conventional learning model; (2) students in the Scientific Paper course who had high levels of self-regulated learning and those who had low levels of self-regulated learning showed significantly higher levels of academic procrastination; and (3) there was an interaction effect between the project-based learning model and self-regulated learning on academic procrastination of students in the Scientific Paper course. It is thought that the growth of SRL will improve academic performance and boost students' accountability for their education. To track the evolution of SRL and the calibre of students' scientific work over time, further longitudinal study can be done. Another possible line of inquiry is the creation of a hybrid learning paradigm that specifically combines SRL training and PBL.